El carro de Ezequiel: la monarquía hispana de fray Buenaventura de Salinas y Córdova - Gálvez Peña, Carlos M. (2008)
A critical reading of the third, and largely unknown, memorial of the Franciscan Buenaventura de Salinas y Córdova (Madrid, 1639) reveals ideas about viceregal economy and politics that are absent from his more famous work, Memorial de las historias del Nuevo Mundo Pirú (Lima, 1630). The 1639 text allows one to establish thematic continuities not only among the writings of his corpus but also with the writings of contemporary authors. Placing Salinas in the ideological context of the seventeenth century thus provides a better understanding of the origin of his ideas. Additionally, this reading discusses the validity of the category of cronista, which has been applied traditionally to Salinas, and proposes for him instead the category of letrado of the early modern period.